Optimizing cytological specimens of EUS‐FNA of solid pancreatic lesions: A pilot study to the effect of a smear preparation training for endoscopy personnel on sample quality and accuracy. Issue 2 (24th October 2020) - van Riet, Priscilla A.; Quispel, Rutger; Cahen, Djuna L.; Erler, Nicole S.; Snijders‐Kruisbergen, Mieke C.; Van Loenen, Petri; Poley, Jan‐Werner; van Driel, Lydi M.J.W.; Mulder, Sanna A.; Veldt, Bart J.; Leeuwenburgh, Ivonne; Anten, Marie‐Paule G.F.; et al.
Abstract: Background: In the absence of rapid on‐side pathological evaluation, endoscopy staff generally "smears" endoscopic ultrasound guided fine needle aspiration (EUS‐FNA) specimens on a glass slide. As this technique is vulnerable to preparation artifacts, we assessed if its quality could be improved through a smear‐preparation‐training for endoscopy staff. Methods: In this prospective pilot study, 10 endosonographers and 12 endoscopy nurses from seven regional EUS‐centers in the Netherlands were invited to participate in a EUS‐FNA smear‐preparation‐training. Subsequently, post training slides derived from solid pancreatic lesions were compared to pre‐training "control" slides. Primary outcome was to assess if the training positively affects smear quality and, consequently, diagnostic accuracy of EUS‐FNA of solid pancreatic lesions. Results: Participants collected and prepared 71 cases, mostly pancreatic head lesions (48%). Sixty‐eight controls were selected from the pretraining period. The presence of artifacts was comparable for smears performed before and after training (76% vs 82%, P = .36). Likewise, smear cellularity (≥50% target cells) before and after training did not differ (44% (30/68) vs 49% (35/71), P = .48). Similar, no difference in diagnostic accuracy for malignancy was detected ( P = .10). Conclusion: In this pilot EUS‐FNA smear‐preparation‐training for endoscopy personnel, smear quality and diagnostic accuracy were not improved after the training. Based on these results, we plan to further study other training programs and possibilities.